An Expressive Analysis of Tulus' Song "Gajah" Lyrics Using a Pragmatic Framework - Ginting, Reza Pahlevi; Azis, Abdul; Ginting, Mutia Suri (Electronic Journal of Education, Social Economics and Technology, 2024)
This study analyzes the linguistic and emotional layers of Tulus' song “Gajah”, focusing on speech acts and implicature in the lyrics and their connection to themes of self-acceptance, social stigma, and identity transformation. Utilizing a qualitative descriptive approach, the research combines expressive and pragmatic critique methodologies to explore how the lyrics communicate personal experiences and emotions. The primary data consists of the song's lyrics and supplementary interviews, articles, and reviews about the song’s creation. By employing documentation, observation, and textual analysis, the study examines various speech acts—representative, directive, expressive, declarative, and commissive- and contextual meanings. The analysis shows that Tulus effectively uses language to convey personal and societal experiences, mainly focusing on how childhood ridicule based on his physical appearance evolves into a message of empowerment and acceptance. Furthermore, the study uncovers implicit meanings (implicature) embedded in the lyrics, illustrating the shift of social stigma into a symbol of strength and pride. The findings suggest that Tulus' lyrics represent a personal journey toward self-acceptance and address broader societal issues, urging listeners to reinterpret mockery as a form of hidden praise. By integrating speech act theory and pragmatic implicature analysis, this study demonstrates how “Gajah” is a powerful vehicle for emotional expression and social critique, ultimately conveying a message of solidarity and personal transformation.